Comparison of Vavoua, Malaise and Nzi traps with and without attractants for trapping of Stomoxys spp. (Diptera: Muscidae) and tabanids (Diptera: Tabanidae) on cattle farms - Tunnakundacha, Sarinyarat; Desquesnes, Marc; Masmeatathip, Roungthip (Agriculture and Natural Resources, 2017)
Insect traps can be used to monitor or collect haematophagous insects. The objective of this study was to compare the efficacy of three insect traps (Vavoua, Malaise and Nzi traps) on two cattle farms in Thailand. In addition, a comparison of olfactive attractants was carried out in pasture. Vavoua traps caught significantly (p < 0.05) higher numbers of Stomoxys spp. than Malaise and Nzi traps, respectively, with daily means of 69.7 ± 13.6, 31.3 ± 26.6 and 32.3 ± 25.8 stomoxes flies in a stable area in Nakhon Pathom province and 79.67 ± 23.71, 46.67 ± 21.55 and 58.33 ± 24.11 in pasture in Kanchanaburi province. Conversely, Nzi traps caught significantly more tabanids than Malaise and Vavoua traps on both farms. The mean daily numbers of insects caught using traps baited with cow urine mixed with dry straw (CUS) significantly increased in Vavoua, Malaise and Nzi traps, respectively, by 2.2 ± 0.9, 1.6 ± 0.5 and 1.8 ± 0.6 for stomoxes flies, and by 3.6 ± 1.8, 3.3 ± 1.7 and 1.8 ± 0.4 for tabanids. Vavoua and Nzi traps baited with CUS could be used on farm and in pasture to contribute to respective reductions in stomoxes and tabanids adult, biting-fly populations.